ANALYSIS OF GENDER DIFFERENCE IN ACADEMIC SELF-EFFICACY AND ACHIEVEMENTS AMONG SENIOR SECONDARY SCHOOL STUDENTS IN NIGER STATE, NIGERIA - Baji, Mohammed Ibrahim (PEOPLE: International Journal of Social Sciences, 2020)
This study examines gender difference in academic self-efficacy and achievements of public senior secondary school students in Niger state, Nigeria. The paper employed descriptive survey design, two research questions and hypotheses. A sample of 435 students for 2017/2018 academic session was selected through proportionate stratified random sampling technique (294 males, 141 females). The Academic Self-Efficacy Scale (ASES) and Academic Achievement Tests in English Language and Mathematics were used as instruments for data collection. The ASES instrument was validated through content and construct validity and the Cronbach’s Alpha method was used to find reliability of the instruments which had a coefficient alpha of .829. The statistical techniques used for data analysis were mean, standard deviation, and t-test independent statistics. The findings of the study found that there was no significant difference in academic self-efficacy between male and female students. However, the mean value of female students indicated a higher level of academic self-efficacy (Mean =78.36) over the male students (Mean =78.16). The study also revealed a significant difference in achievements of male and female students. The mean difference showed that the male students performed better in academic achievements if compared with their female counterparts (Mean =105.42 for males and Mean =100.58 for females). The study recommended parental support and encouragement, provision of scholarship and sponsorship for female students, free girl-child education, and employment opportunities for females, among others as strategies by governments at all levels and non-governmental organizations to boost self-efficacy of male students and bridge the gap that exist in achievements between male and female students in Niger state, Nigeria.